Gender-affirming DIEP Flap Breast Augmentation - Ian T. Nolan, MD; Brandon E. Alba, MD; Brielle Weinstein, MD; Loren S. Schechter, MD; Deana S. Shenaq, MD; David E. Kurlander, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Implant-based techniques have been the mainstay of gender-affirming breast augmentation (GABA). Here we describe a novel autologous technique for GABA. We provide a single-patient case report of gender-affirming deep inferior epigastric artery perforator (DIEP) flap breast augmentation. World Professional Association for Transgender Health guidelines were followed according to Standards of Care, version 8. Prepectoral tissue expanders were placed at the time of the patient’s facial feminization surgery. DIEP flaps were then used for bilateral breast augmentation. Planned revisions were made about 5 months later. Breast augmentation was performed successfully with DIEP flaps, and the patient was satisfied with her outcome. No complications occurred. Anatomic differences to cisgender women were noted, including relatively thick musculature of the abdominal wall and chest as well as tight anterior abdominal fascial closure. Advantages compared with implant-based GABA were also noted, including feminization of the abdomen and avoidance of potential implant related complications. We report a novel approach to GABA. Our approach borrows well-established techniques with demonstrated efficacy and high satisfaction in postmastectomy breast reconstruction and even cosmetic purposes. However, sex- and hormone-influenced anatomic differences required some modifications compared with postmastectomy DIEP flap reconstruction.